ENHANCING ENGLISH LANGUAGE PROFICIENCY IN MALAYSIA: THE MATTFAWY PROJECT - WAN HURANI OSMAN; ANNA LYNN ABU BAKAR (MANU Journal of Humanities, 2024)
Abstract The discourse on English language proficiency in Malaysia represents a significant challenge for educators and industry professionals. Malaysian learners encounter a multitude of obstacles, notably psychological barriers such as anxiety and low self-confidence. These issues are exacerbated by graduates’ reluctance to engage in English-speaking practices, leading to subpar oral skills. Moreover, traditional teaching methodologies that prioritise grammar and vocabulary are increasingly seen as outdated in the face of today’s digital literacy demands. In response to these educational challenges, the MaTTFaWY project was developed, incorporating digital platforms - Madlipz, TikTok, Facebook, Word of Wonders, and YouTube - to create a more dynamic language learning experience. This project is a component of an Oral Communication in English course and is grounded in an integrative teaching approach, blending connectivism, which recognises the profound influence of technology on learning, with constructivism, focusing on experiential learning and peer interaction. The MaTTFaWY initiative strives to bolster English language proficiency in the classroom and in students’ everyday lives. This paper explores the framework of MaTTFaWY and presents initial evidence of its success. According to students’ feedback and performance assessments, MaTTFaWY has improved students’ speaking skills, self-efficacy, self-esteem, creativity, confidence, and motivational levels. These enhancements suggest that MaTTFaWY is an effective strategy for navigating the complexities of the English language, marking a progressive step towards more immersive and technologically integrated language learning environments.